Early angiogenesis detected by PET imaging with 64Cu-NODAGA-RGD is predictive of bone critical defect repair. (December 2018) - Collignon, Anne-Margaux; Lesieur, Julie; Anizan, Nadège; Azzouna, Rana Ben; Poliard, Anne; Gorin, Caroline; Letourneur, Didier; Chaussain, Catherine; Rouzet, Francois; Rochefort, Gael Y.
Graphical abstract: Abstract: Therapies using stem cells may be applicable to all fields of regenerative medicine, including craniomaxillofacial surgery. Dental pulp stem cells (DPSCs) have demonstrated in vitro and in vivo osteogenic and proangiogenic properties. The aim of the study was to evaluate whether early angiogenesis investigated by nuclear imaging can predict bone formation within a mouse critical bone defect. Two symmetrical calvarial critical-sized defects were created. Defects were left empty or filled with i) DPSC-containing dense collagen scaffold, ii) 5% hypoxia-primed DPSC-containing dense collagen scaffold, iii) acellular dense collagen scaffold, or iv) left empty. Early angiogenesis assessed by PET using 64 Cu-NODAGA-RGD as a tracer was found to be correlated with bone formation determined by micro-CT within the defects from day 30, and to be correlated to the late calcium apposition observed at day 90 using 18 F-Na PET. These results suggest that nuclear imaging of angiogenesis, a technique applicable in clinical practice, is a promising approach for early prediction of bone grafting outcome, thus potentially allowing to anticipate alternative regenerative strategies. Statement of Significance: Bone defects are a major concern in medicine. As life expectancy increases, the number of bone lesions grows, and occurring complications lead to a delay or even lack of consolidation. Therefore, to be able to predict healing or the absence of scarring at early times would be very interesting. This would not "waste time" for the patient. We report here that early nuclear imaging of angiogenesis, using 64 Cu-NODAGA-RGD as a tracer, associated with nuclear imaging of mineralization, using 18 F-Na as a tracer, is correlated to late bone healing objectivized by classical histology and microtomography. This nuclear imaging represents a promising approach for early prediction of bone grafting outcome in clinical practice, thus potentially allowing to anticipate alternative regenerative strategies.